Upper limb injuries in mixed martial arts - Fares, M. Y.; Baydoun, H.; Elhassan, B.; Abboud, J. A. (The Physician and Sportsmedicine, 2023)
Objective Mixed-Martial-Arts(MMA) is a worldwide growing sport that incorporates different fighting styles and disciplines and is often associated with the Ultimate Fighting Championship(UFC) . The aim of this study is to explore the patterns and trends of upper limb injuries in MMA.